Role of innovation networks to support the livestock extension systems of Pakistan - Warriach, Hassan Mahmood (University of Melbourne, 2019)
Presented by Hassan Mahmood Warriach (The University of Melbourne), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.